UM memory: pemasyarakatan warisan sejarah - Tamjehi, Haslan; Yusof, Mahbob (Persatuan Pustakawan Malaysia, 2013)
UM Memory is a digital archive which provides a platform to store and manage the University of Malaya historical photos.It was developed in 2011 as one of UM Library's digital initiatives in line with the current trend to leverage social media to connect with users. Hence, UM Memory initiative utilizes social media in socializing more than 3000 photos in the archive. This article will discuss the specification of its social media functions in the implementation stage within UM Memory as well the general outline of its socialization approach. Together, this article demonstrates that this effort is a viable approach to take UM Memory to the international level and become daily conversational topics among societies at large. The socialization approach has shifted the library services delivery, access and library collection dissemination. It changes the conventional outlook of collection delivery for reference and research to social media utilization as a channel to converse and share topics on the collection by the public.